Aktualisasi Kualitas Layanan Tata Usaha dalam Pengelolaan Administrasi : Studi Kasus MTs Darussalam Parigi Baru Kecamatan Pondok Aren Kota Tangerang Selatan - Erika Damayanti; Mohammad Muhtadi; Abdul Kholiq (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to analyze the actualization of administrative service quality in managing school administration at MTs Darussalam Parigi Baru, Pondok Aren District, South Tangerang City, including service implementation, challenges encountered, and improvement efforts. This research employed a qualitative approach using a case study method through observation, interviews, and documentation involving the head of administration, administrative staff, teachers, and students. Data were analyzed through data reduction, data presentation, and conclusion drawing. The findings indicate that administrative services have been implemented reasonably well through the application of excellent service principles, including reliability, responsiveness, responsibility, and effective communication in correspondence and student administration services. However, several challenges remain, such as limited human resources, partially manual filing systems, inadequate administrative facilities, and the absence of well-established standard operating procedures (SOPs). Improvement efforts have been carried out through strengthening work coordination, enhancing staff discipline, and developing a more structured administrative system. This study concludes that the quality of administrative services plays a strategic role in supporting administrative effectiveness and improving the quality of educational services in madrasahs.